Application of Ultrasonography During Sternocleidomastoid Muscle Release for Congenital Muscular Torticollis: A Case Report. Issue 4 (14th October 2021) - Choe, Hyonmin; Kobayashi, Naomi; Oba, Masatoshi; Morita, Akira; Abe, Koki; Inaba, Yutaka
Abstract : Case: We report a 4-year-old girl with congenital muscular torticollis (CMT) who was treated with sternocleidomastoid muscle (SCM) tenotomy using ultrasonography (US). Prior to the surgery, US was utilized to identify the clavicle and sternum branches of the SCM, sternohyoid muscles, internal jugular vein, and common carotid artery. Then, local anesthesia was injected into the layer between the fascial sheath of the SCM and carotid sheath to reduce bleeding and avoid vascular injury. During surgery, the SCM dissection was carefully conducted under US guidance to avoid vascular injury. No residual of SCM dissection and improvement of neck motion were confirmed before the skin closure. Postoperative course was good with no obvious complications in this patient. Conclusion: The intraoperative US investigation during SCM tenotomy is a useful procedure that provides vital information about dissection area of SCM and orientation of internal jugular vein that reduces the risk of insufficient tenotomy and vascular injury.